ESTRUCTURA Y COMPOSICIÓN DE 1 HA. DE BOSQUE EN UN FRAGMENTO CERCA A LAGO AGRIO, SUCUMBÍOS-ECUADOR - Cerón, Carlos (2005)
The study area is located in Lago agrio county, Sucumbios Province, 10 Km of the Lago agrio - El Coca Road, 2 Km before the river Aguanco bridge, 76°48.332W -00°03.342N , coordenates, 330 m altitude, Tropical humid forest zone of life. Lowland evergreen forests. Field work was done December, 2000 in a little hill, we set up a plot of 100 x 100 m . (1 Ha.). The trees > 10 cm of DAP were marked with metallic chips , we collected herbarium examples, assembled and indentified them The examples are deposited at the herbanum QAP We calculated the Basal Area (AB) and the Important Value Index (IVI) of the species, genera and families. In the study we found: 654 individual, 245 old trees. 131 genera, 49 families The Basal Area a total of 29.74 m2 The four more important species, genera and families m the plot according with the frecuency. IVI were Rinorea apiculata (70 individuals. IVI = 16.6). Iriartea deltoides (41 individuals. IVI « 9.67). Cecropia sciadophylla Cinchonia Vol. 6, # 1, 2005 57 (18 individuals, IVI = 8.39) and Zygia sp. 1 (16 individuals, IVI = 6.37), in genera: : Rinorea. Iriartea, Inga and Cecropia, in families: by the Violaceae frecuency (73 individuals), Arecaceae (47), Mimosaceae (51), Moraceae (47) and according with the IVI: Moraceae (IVI=20.52), Violaceae (IVI=17.25), Mimosaceae (IV I=16.82) and Cecropiaceae (IVI=12.87). The diversity of plot, the inusual domain of Rinorea apiculata, the presence of Cecropiaceae between the first domain families. shows some disturbs in the forest and the location of the forest fragment between the field and the small farm close to Lago Agrio in a antique terrace of the Aguarico river, caracterize the present study and make us suppose that other locality across of the deep valley that river will be equal in diverse to the River Napo deep valley. The study area is located in Lago agrio county, Sucumbios Province, 10 Km of the Lago agrio - El Coca Road, 2 Km before the river Aguanco bridge, 76°48.332W -00°03.342N , coordenates, 330 m altitude, Tropical humid forest zone of life. Lowland evergreen forests. Field work was done December, 2000 in a little hill, we set up a plot of 100 x 100 m . (1 Ha.). The trees > 10 cm of DAP were marked with metallic chips , we collected herbarium examples, assembled and indentified them The examples are deposited at the herbanum QAP We calculated the Basal Area (AB) and the Important Value Index (IVI) of the species, genera and families. In the study we found: 654 individual, 245 old trees. 131 genera, 49 families The Basal Area a total of 29.74 m2 The four more important species, genera and families m the plot according with the frecuency. IVI were Rinorea apiculata (70 individuals. IVI = 16.6). Iriartea deltoides (41 individuals. IVI « 9.67). Cecropia sciadophylla Cinchonia Vol. 6, # 1, 2005 57 (18 individuals, IVI = 8.39) and Zygia sp. 1 (16 individuals, IVI = 6.37), in genera: : Rinorea. Iriartea, Inga and Cecropia, in families: by the Violaceae frecuency (73 individuals), Arecaceae (47), Mimosaceae (51), Moraceae (47) and according with the IVI: Moraceae (IVI=20.52), Violaceae (IVI=17.25), Mimosaceae (IV I=16.82) and Cecropiaceae (IVI=12.87). The diversity of plot, the inusual domain of Rinorea apiculata, the presence of Cecropiaceae between the first domain families. shows some disturbs in the forest and the location of the forest fragment between the field and the small farm close to Lago Agrio in a antique terrace of the Aguarico river, caracterize the present study and make us suppose that other locality across of the deep valley that river will be equal in diverse to the River Napo deep valley.